The village effect : how face-to-face contact can make us healthier, happier, and smarter - Pinker, Susan, 1957- (New York : Spiegel & Grau, 2014)
From birth to death, human beings are hard-wired to connect to other human beings. Social networks matter: tight bonds of friendship and love heal us, help us to learn and remember, extend our lives and make us happy. But not just any social networks: we need the real, face-to-face, in-the-flesh encounters that tie human families, groups of friends and communities together. Marrying the findings of the new field of social neuroscience together with gripping human stories, developmental psychologist Susan Pinker explores the impact of face-to-face contact from cradle to grave, from city to Sardinian mountain village, classroom to workplace, from love to marriage to divorce. Most of us have left the literal village behind, and don't want to give up our new technologies and go back there. But, Pinker writes, we need close social bonds and uninterrupted face-time with our friends and families in order to thrive -- even to survive. Creating our own "village effect" can make us happier. It can also save our lives.
Introduction: People who need people -- Swimming through the school of hard knocks: How social bonds can rejig the outcome of chronic disease -- It takes a village to raise a centenarian: Longevity as a team sport -- A thousand invisible threads: Face-to-face contact and social contagion -- Who's coming to dinner: Food, drink, and social bonds -- Baby chemistry: How social contact transforms infants' brains -- Digital natives: Electronic devices and children's language development, school progress, and happiness -- Teens and screens: How digital technology has transformed teens' lives -- Going to the chapel: Face-to-face social networks, love, and marriage -- When money really talks: Social networks, business, and crime -- Conclusion: Creating the village effect.
Includes bibliographical references (pages 289-350) and index.
Keywords: Social interaction -- Health aspects; Interpersonal relations; Interpersonal communication; Eye contact; Quality of life; PSYCHOLOGY -- Interpersonal Relations; SELF-HELP -- General; PSYCHOLOGY -- General; Eye contact; Interpersonal communication; Interpersonal relations; Quality of life; Social interaktion